Factors Associated With Poor Outcome in Childhood Swimming Pool Submersions. Issue 10 (October 2016) - Shenoi, Rohit P.; Koerner, Christine E.; Cruz, Andrea T.; Frost, Mary H.; Jones, Jennifer L.; Camp, Elizabeth A.; Alam, Sartaj; Fraser, John J.
Abstract : Objectives: The aims of the study were to determine factors associated with poor outcome in childhood swimming pool submersions and to study the association of bystander resuscitation with clinical outcome. Methods: This was a retrospective study of swimming pool submersion victims younger than 18 years in a metropolitan area from 2003 to 2007. Submersion, prehospital, and victim data were obtained from hospital, Emergency Medical Services, and fatality records. Outcome based on survival at hospital discharge was favorable (baseline/mild impairment) or poor (death/severe impairment). Logistic regression determined factors associated with poor outcome. Results: There were 260 submersions. Outcomes were available for 211 (81%). The median age was 4 years; 68% were males. Most incidents occurred at single residential pools (48%) and multiresidential pools (35%). Mortality was 23%; 75% had favorable outcomes. Favorable outcomes occurred in 8.6% (3/35) of victims with absent pulse at the scene. Descriptive analyses revealed significant differences in submersions that occurred on weekdays, during the summer, submersions lasting 5 minutes or more, with on-scene apnea or cardiac arrest needing cardiopulmonary resuscitation, rescuer type, and transfer to tertiary care. Logistic regression revealed that poor outcome was significantly associated with prolonged submersions and those that occurred on a weekday. Furthermore, hospitalization reduced the odds of a poor outcome by 81% when compared with victims who were not hospitalized. Bystander resuscitation was not significantly associated with outcome. Conclusions: Childhood swimming pool submersions, which occur on weekdays and with prolonged submersion times, are associated with poor outcome. Bystander resuscitation is not significantly associated with outcome.